2012
DOI: 10.1614/ws-d-11-00160.1
|View full text |Cite
|
Sign up to set email alerts
|

Tabanone, a New Phytotoxic Constituent of Cogongrass (Imperata cylindrica)

Abstract: Cogongrass is a troublesome, invasive weedy species with reported allelopathic properties. The phytotoxicity of different constituents isolated from roots and aerial parts of this species was evaluated on garden lettuce and creeping bentgrass. No significant phytotoxic activity was detected in the methylene chloride, methanol, or water extracts when tested at 1.0 mg ml−1. However, the total essential oil extract of cogongrass aerial parts was active. Bioactivity-guided fractionation of this extract using silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Of the 12 studies that investigated allelopathy, 11 used either pulverized tissues or leachate and only one utilized soils from an established cogongrass population. Most allelopathy trials were conducted on crop species (e.g., cucumber, tomato, rice), and all but one study (Cerdeira et al, 2012) reported negative effects on germination and/or growth rates of test species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 12 studies that investigated allelopathy, 11 used either pulverized tissues or leachate and only one utilized soils from an established cogongrass population. Most allelopathy trials were conducted on crop species (e.g., cucumber, tomato, rice), and all but one study (Cerdeira et al, 2012) reported negative effects on germination and/or growth rates of test species.…”
Section: Resultsmentioning
confidence: 99%
“…There are a wide variety of possible explanations for the invasive success of cogongrass. For example, the ability of the species to establish and persist in highly variable habitats has been attributed to dense rhizome formation (Dozier et al, 1998;MacDonald, 2004), allelopathy (Cerdeira et al, 2012;Hagan et al, 2013b), high rates of reproduction through both seeds and rhizomes (Holly and Ervin, 2007), exceptional phenotypic plasticity (Patterson, 1980), and tolerance of diverse growing conditions including shade, drought, and poor soil quality (Bryson et al, 2010;Patterson, 1980). In addition, fire, cultivation, or other anthropogenic disturbances are also thought to promote cogongrass invasions ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The major phytochemical constituents identified in I. cylindrica are phenylpropanoids [2], lignan glycosides [3], biphenyl ethers [4], sesquiterpenoids [5], phenolic compounds [6], lignans [5], and megastigmatrienone [7].…”
Section: Introductionmentioning
confidence: 99%
“…While cogongrass has great spiritual and medicinal signiicance to Vedic cultures on the Indian sub-continent, it is suggested that more of the phytotoxic properties should be tested as alternatives to synthetic chemical treatments that result in negative impacts to the environment [146]. Because this plant spreads aggressively by rapidly growing rhizomes, there is potential to derive social value through mechanical management that harvests the roots for processing, rather than using herbicides to kill it outright, and harm the environment.…”
Section: Case Study 2: Cogongrass (Imperata Cylindrica [L] Beauv)mentioning
confidence: 99%